Exploring Inter-Banking Conflicts: Evidence from Bangladesh - Zoynul, Abedin Mohammad; Chi, Guotai; E–Moula, Fahmida (Economic Journal of Nepal, 2015)
This paper seeks to investigate the causes of conflicts at banking industry as until now, no work, as per our best knowledge, were conducted in Bangladesh about the inter – banking conflicts. The study explored factors liable for inter banking conflicts and their impact on banking environments and to examine that how conflicts affect both employers and employees. The results were analyzed through two steps. At the first step, mean, standard deviation and Pearson Bivariate correlationwere used, following by chi – square test and t – test at the second step. The study revealed multiple factors are responsible for conflicts within the banks that affect employee’s work environment and their performance. A total of 80 questionnaires were distributed at 13 commercial banks and 5 Islami banks in Dhaka and a total of 75 questionnaires were found. From the result of the findings it is clear that conflict in banking industry affect the social and economic environment of Bangladesh and it is strongly advised that such type conflicts should not be extended to bank customers, as this will create adverse effect on the volume of banking business. The Economic Journal of Nepal, Vol. 35, No. 2, April-June 2012 (Issue N0. 138)